Samoa : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Samoa. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
KEY ISSUES Outlook and risks. Growth is recovering gradually from natural disasters and inflation remains subdued. The current account deficit is expected to narrow on lower international oil prices and a planned fiscal consolidation. The main external risk is the occurrence of another natural disaster in the presence of already high public debt and vulnerabilities in financial institutions. The main domestic risks center around a delay in rebuilding macroeconomic buffers, in particular through fiscal consolidation, reforms of public financial institutions and financial oversight. Improving financial resilience. A recent financial sector assessment program (FSAP) mission identified risks in some commercial banks and public financial institutions (PFIs). The role of PFIs needs to be refocused to reduce contingent liabilities for public finances and to support the development of private financial markets. Regulation and supervision of financial institutions needs to be improved to reduce the risk of an adverse feedback loop from banks and PFIs to the public finances in case of another external shock. Rebuilding macroeconomic buffers. A gradual fiscal consolidation is planned to reduce public debt to the target of 50 percent of GDP by 2020, mainly through improvements in revenue and a reduction in current expenditure. While there is no significant evidence of misalignment, and reserves are adequate by standard metrics, a stronger external position with higher reserves would provide greater resilience. Boosting growth. The authorities' structural reform initiatives emphasize a revitalization of agriculture and food processing, tourism, and an enabling environment for business. Reforms to SOE governance are beginning to bear fruit, but the government should stay the course in planned privatizations and amendments to legislation to reduce the burden of state-owned enterprises (SOEs) on the public finances. Improvements in financial infrastructure will improve the flow and allocation of credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet